Estimation of tree water stress from stem and soil water monitoring with timeâ€domain reflectometry in two small forested basins in Spain (Hydrological P, 2008)
Soil-tree water relationships were studied using time domain reﬂectometry (TDR) in two small forested basins in Spain. The stem water content of two Mediterranean Quercus species (Quercus pyrenaica and Quercus rotundifolia) was measured using previously constructed species-speciﬁc equations. To monitor soil moisture, a TDR station network was used in both cases. Sixteen Q. pyrenaica and six Q. rotundifolia individuals were selected to install two TDR probes in their trunks (at 20 and 120 cm above the ground) to monitor stem water content. Stem and soil water contents were measured fortnightly. The stem water content of both species showed a similar temporal trend for the period studied. A spring maximum (0Ð654 cm3 cm3 for Q. pyrenaica and 0Ð568 cm3 cm3 for Q. rotundifolia) was found to be associated with high transpiration and no soil moisture deﬁcit, and a late-summer minimum (0Ð520 cm3 cm3 for Q. pyrenaica and 0Ð426 cm3 cm3 for Q. rotundifolia) was associated with the end of the dry season. This drop in stem water content occurs when the available water in the soil decreases. This seasonal difference presumably reﬂects water withdrawn from stem storage to support the transpirational demands of the tree. Since plant water stress results in reduced stem water content and since this drop can be measured by TDR, it may be concluded that this technology offers a suitable tool for detecting plant water stress

TDR measurement of stem and soil water content in two Mediterranean oak species (Hydrological Sciences Journal, 2008)
Abstract Since 1990s, time domain reflectometry (TDR) has been applied to estimate the stem water content of living trees. Here, new calibration equations relating the apparent dielectric constant (Ka ) to the volumetric water content (?) were developed for two Mediterranean oak species. Our calibration equations differ from those previously calculated for other species, suggesting that stem water contents could be monitored more accurately using species-specific curves. The stem water content in the trees of these species and the surrounding soil were monitored with TDR to examine the feasibility of this technology for recording changes in trunk water storage. The average stem water contents of the oaks reflect the soil water contents, and the temporal differences observed (17%) point to the importance of trunk water for coping with soil water deficit. Although it would be very useful to obtain a single function to estimate the stem water content of trees, it remains necessary to obtain the results in more species.
doi: 10.1623/hysj.53.4.921

TDR measurement of stem and soil water content in two Mediterranean oak species - HERNÁNDEZ-SANTANA, VIRGINIA; MARTÍNEZ-FERNÁNDEZ, JOSÉ (Hydrological Sciences Journal, 2008)
Abstract Since 1990s, time domain reflectometry (TDR) has been applied to estimate the stem water content of living trees. Here, new calibration equations relating the apparent dielectric constant (Ka ) to the volumetric water content (?) were developed for two Mediterranean oak species. Our calibration equations differ from those previously calculated for other species, suggesting that stem water contents could be monitored more accurately using species-specific curves. The stem water content in the trees of these species and the surrounding soil were monitored with TDR to examine the feasibility of this technology for recording changes in trunk water storage. The average stem water contents of the oaks reflect the soil water contents, and the temporal differences observed (17%) point to the importance of trunk water for coping with soil water deficit. Although it would be very useful to obtain a single function to estimate the stem water content of trees, it remains necessary to obtain the results in more species.
doi: 10.1623/hysj.53.4.921doi: 10.1623/hysj.53.4.921The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Quercus pyrenaica; Quercus rotundifolia; Soil moisture; stem water content; TDR